Um estudo sobre o processo de ensino e aprendizagem nos anos iniciais do ensino fundamental e o tema transversal ética - Coelho, Bruna Serra (Brasil, 2024)
A Study on the Teaching and Learning Process in the Early Years of Elementary Education and the Transversal Theme of Ethics," the problem approach is qualitative in nature, with the study being descriptive, documentary, and observational. The physical setting is a Municipal School located in the Central-West Zone of the city of Manaus. The techniques and instruments used for data collection included the analysis of the curricular proposal for elementary education in the early years by the Municipal Department of Education (SEMED), direct observation in the school context, and semi-structured interviews with the school's teachers. The main objective is to reflect on how the formation of ethical principles in children has been methodologically addressed in the teaching and learning process in the early years of elementary education. This research stems from the pressing need to highlight how socially constructed ethical principles, proposed and recommended in the National Curriculum Parameters (PCN), particularly in the section on the Transversal Theme of Ethics, are being shaped during the early years of schooling. As is well known, ethics is an integral part of the social coexistence of individuals, whose practices materialize in everyday actions, fostering the expansion and/or degradation of their moral consciousness, as well as their development as participants in a given society. However, this moral development, essential for equitable coexistence in society, does not seem to unfold as expected in our democratic society, given the ethical deviations observed and reported daily. Thus, it became necessary for us to reflect on these daily actions, which implicate future ethical stances. The results indicate that, in the school’s daily life, there is still a significant gap between what is proposed in the PCN on ethics and the role of the school in planning and ensuring activities that encourage children, from an early age, to reflect on their behavior and that of their peers in everyday social situations, considering principles that are assimilated rather than based on standardized formulas. The degrading social reality currently unfolding constitutes a strong appeal for the school institution to pay more intentional attention to the ethical formation of young students. This is crucial given the constant encounters with numerous situations that challenge the meaning of ethics in adult life in society.